Influence of Different Water Vapor Sources on the Precipitation Processes on the Qinghai-Xizang （Tibet） Plateau in Summer - Changrui ZHU; Minhong SONG; Shaobo ZHANG; Longtengfei MA (Gaoyuan qixiang)
Based on the knowledge that the main sources of summer water vapor on the Qinghai-Xizang （Tibet） Plateau are the Arabian Sea， the Bay of Bengal， and the South China Sea， a simulation study of the effects of different water vapor sources on the eastern-type and western-type precipitation on the Qinghai-Xizang （Tibet） Plateau in summer was carried out.Numerical simulations of water vapor content reduction at different water vapor source locations were conducted using conventional observations， NCEP/NCAR global reanalysis data， and the mesoscale numerical model WRF for two intense precipitation processes on the Qinghai-Xizang （Tibet） Plateau from June 28 to July 2， 2016 （eastern type） and from July 19 to 23， 2018 （western type）， by separately integrating the Arabian Sea， Bay of Bengal， and South China Sea By comparing three sets of sensitivity experiment and control experiment， the relative humidity at the Arabian Sea， the Bay of Bengal and the South China Sea was reduced by 70%， 60%， 50%， 40% and 30% from the ground to 100hPa respectively， and the effects of the reduction of water vapor content at different water vapor sources on summer precipitation on the plateau were explored in depth from the perspectives of circulation field， water vapor transport and precipitation changes， and the following main conclusions were obtained： （1） The reduction of water vapor content at three water vapor sources has an effect on The reduction of water vapor over the Bay of Bengal significantly reduced the summer precipitation of the Qinghai-Xizang （Tibet） Plateau by about 10% in 2016 （eastern type） and 2018 （western type） compared with the controlled experiment， while the reduction of water vapor over the South China Sea had minimal effects on the two summer precipitation processes of the Qinghai-Xizang （Tibet） Plateau.Reducing the water vapor over the Arabian Sea plays a catalytic role in the precipitation of the western type of the plateau， increasing the precipitation by about 10% relative to the controlled test； and inhibiting the precipitation of the eastern type of the plateau， making the precipitation decrease by about 5% relative to the controlled test.（2） Changing the water vapor conditions over the Bay of Bengal source has the most obvious effect on the precipitation on the Qinghai-Xizang （Tibet） Plateau.The possible reason is that reducing the water vapor conditions over the Bay of Bengal makes the low value system on the southern side of the plateau weaken， and the southerly wind on the plateau weakens， resulting in weaker water vapor transport， resulting in less precipitation on the plateau.（3） The difference of water vapor revenue and expenditure in the plateau region was not obvious in the control experiment and three sensitivity experiment at the beginning of the simulation， but with the increase of simulation time （after about 48 h）， there were obvious differences in water vapor revenue and expenditure in the Qinghai-Xizang （Tibet） Plateau， and there was an obvious correlation between water vapor revenue and expenditure and daily precipitation.